Transient probabilities for a simple birth-death-immigration process under the influence of total catastrophes. (8th March 2001) - Swift, Randall J.
Abstract : The transient probabilities for a simple birth-death-immigration process are considered. Catastrophes occur at a constant rate, and when they occur, reduce the population to size zero.